A review of mitochondrial dysfunction in diabetic sarcopenia: Mechanisms, diagnosis, and treatment approaches - Zhilin Xie; Yuanhao Li; Xiaoliu Li; Jing Zhang (Journal of International Medical Research)
Diabetic sarcopenia is a common complication of diabetes, substantially impacting patients’ quality of life and prognosis. Its pathogenesis is closely related to energy metabolism, with mitochondria—often referred to as the cellular “powerhouse”—playing a central role in this process. This review focuses on the role of mitochondrial dysfunction in diabetic sarcopenia, emphasizing mechanisms such as energy metabolism imbalance, oxidative stress–induced damage, and abnormalities in mitochondrial biogenesis and dynamics. Additionally, we discussed current research on diagnostic and therapeutic strategies targeting mitochondrial dysfunction. This narrative review aims to provide a theoretical foundation for a deeper understanding of the pathophysiology of diabetic sarcopenia and the development of novel therapeutic approaches.